Space, time and the post-modern Brazilian cinematic city: interrelations between the cinema and cultural geography (Brazilian Geographical Journal, 2017)
This paper comments on a diversity of concepts drawn from different authors and on David Harvey's concept of ''time-space compression' to set a discussion around the matter of cities and films or, rather, the different ways cities have been represented in films and in what sense the diversity of representations have affected the understanding of the cities themselves. Moreover, thinking about the post-modern condition, this paper will also discuss contemporary Brazilian cinema production by looking at the representation of urban space and violence and its connection to the production of new paradigms for representing space (and time) and understanding cultural identity within post-modernity. It will also present an analysis of the cinematic representation of two Brazilian cities: Rio de Janeiro, in Redentor (Redeemer, Cláudio torres, 2004) and São Paulo in O Homem do Ano (The Man of the Year, José Guilherme Fonseca, 2002).